Analisis Penjualan Dengan Menggunakan Sistem Pembayaran Digital Untuk Meningkatkan Pendapatan Umkm Molases Tetes Tebu - Vera Putri Nasyati; Sari Marliani; July Yuliawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine and analyze sales using a digital payment system on PD income. Nasep Jaya. The research was carried out at PD. Nasep Jaya, whose address is Jl. Raya Pantura Gempolsari, Simpang Village, Patokbeusi District, Rancamulya Village, Subang Regency, West Java. This research uses a qualitative descriptive approach with interview and field observation methods. The form of triangulation used in this research is source triangulation. The results of the research show 1) Sales growth is quite stable, especially around 80% of consumers subscribe every month. Although the use of digital payment systems has not had a significant impact on sales figures. This implementation succeeded in increasing service efficiency and transaction speed. 2). PD digital payment system. Nasep Jaya uses M-Banking, QRIS, and the marketplace platform as a digital payment system through the Shopee e-commerce application. However, economically, more competitive online selling prices provide benefits even though admin discounts of around 3% for Shopee, 0.7% QRIS, and Rp. 6,500 for interbank transfers. The use of M-Banking facilitates transactions efficiently, QRIS provides a faster and easier payment method, while the presence on e-commerce platforms, such as Shopee, expands market reach. 3) Molasses income from molasses using a digital payment system has increased from 2021 before using a digital system to 2022 after using digital by 8%. Digital payment technology is the key to increasing transaction efficiency and stimulating income growth Keywords: Digital Payments, Income, MSMEs, Sales